Penatalaksanaan Holistik Pada Penjahit Perempuan Usia 42 Tahun Dengan Carpal Tunnel Syndrome (CTS) Melalui Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Natar - Utami, Putu Urvasi Ari; Mayasari, Diana; Santika, Maya (CV. Jasa Sukses Abadi, 2025)
Carpal Tunnel Syndrome (CTS) is a peripheral nerve disorder caused by compression of the median nerve at the wrist, classified as a musculoskeletal disorder (MSD) with symptoms such as pain, tingling, and numbness, commonly triggered by ergonomic risk factors in the workplace. The management of CTS requires a comprehensive family medicine-based approach to improve treatment outcomes and the patient’s quality of life. This study aims to implement integrated family medicine principles in examining internal and external risk factors, medical problems, and patient management strategies based on Evidence-Based Medicine (EBM) with a patient-centered, family-oriented, and community-based approach. The research method is a descriptive case report using primary data from interviews, physical examinations, and home visits, as well as secondary data from the medical records of Kedaton Primary Health Center, evaluated holistically through quantitative and qualitative methods. The results showed that a 42-year-old female patient, Mrs. M, with CTS was managed comprehensively with analgesics, vitamins, and poster-based educational interventions; evaluation indicated improved symptoms, increased patient understanding as evidenced by pre- and post-test scores, and enhanced family support. In conclusion, the application of family medicine approaches supports holistic and comprehensive management of CTS patients to identify internal and external risk factors, improve therapeutic success, and enhance patient well-being.